2020
DOI: 10.14814/phy2.14361
|View full text |Cite
|
Sign up to set email alerts
|

Carotid chemoreflex and muscle metaboreflex interact to the regulation of ventilation in patients with heart failure with reduced ejection fraction

Abstract: Synergism among reflexes probably contributes to exercise hyperventilation in patients with heart failure with reduced ejection fraction (HFrEF). Thus, we investigated whether the carotid chemoreflex and the muscle metaboreflex interact to the regulation of ventilation (normalV˙E) in HFrEF. Ten patients accomplished 4‐min cycling at 60% peak workload and then recovered for 2 min under either: (a) 21% O2 inhalation (tonic carotid chemoreflex activity) with legs’ circulation free (inactive muscle metaboreflex); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Fifth, during whole body exercise, the exercise pressor reflex works in concert with various other autonomic control signals which contribute to the sympathetic and cardiovascular adjustments to exercise in health and disease. For example, central command (Koba et al., 2006), the carotid chemoreflex (Li et al., 2006; Machado et al., 2020; Stickland et al., 2007) and the arterial baroreflex (Mancia et al., 1992; Grassi et al., 1995) have all been reported to contribute to sympathetic and cardiovascular responses during exercise. The extent to which ASIC1a contributes to the sympathetic and cardiovascular adjustments to whole body exercise when all these autonomic control mechanisms are working together remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, during whole body exercise, the exercise pressor reflex works in concert with various other autonomic control signals which contribute to the sympathetic and cardiovascular adjustments to exercise in health and disease. For example, central command (Koba et al., 2006), the carotid chemoreflex (Li et al., 2006; Machado et al., 2020; Stickland et al., 2007) and the arterial baroreflex (Mancia et al., 1992; Grassi et al., 1995) have all been reported to contribute to sympathetic and cardiovascular responses during exercise. The extent to which ASIC1a contributes to the sympathetic and cardiovascular adjustments to whole body exercise when all these autonomic control mechanisms are working together remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…First, the EPR is one of the several autonomic control signals that likely contributes to the aberrant sympathetic and cardiovascular adjustments to exercise in HF‐rEF. For example, central command (Koba et al, 2006 ), the carotid chemoreflex (Li et al, 2006 ; Machado et al, 2020 ; Stickland et al, 2007 ), and the arterial baroreflex (Grassi et al, 1995 ; Mancia et al, 1992 ) have all been reported to contribute to aberrant sympathetic and cardiovascular responses during exercise in HF‐rEF. Whether TxA 2 ‐Rs contribute to exaggerated increases in SNA during exercise in HF‐rEF patients when all these autonomic control mechanisms are working in concert with one another (i.e., during whole body exercise) remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This implies the existence of an interaction between the chemoreflex and metaboreflex that might contribute to the hyperventilation during exercise, and any method of reducing the interaction could, theoretically, lead to tangible benefit for patients. This interesting study (Machado et al, 2020) has continued the recent resurgence of interest in ventilatory control during exercise by examining the possible synergistic interactions between different control pathways. In my opinion, this is a very exciting area of research for both physiologists and clinical scientists.…”
Section: Introductionmentioning
confidence: 95%
“…However, if synergistic interactions exist between respiratory control inputs, we should not examine the mechanisms in isolation; abnormalities might be reflected in their central integration, and this understanding might lead to new therapies. For example, Machado et al (2020) assessed the interaction between muscle metaboreflex activation (PECO after cycling exercise) and the carotid chemoreflex in heart failure. They demonstrated a suppressed ventilatory response to PECO during conditions of hyperoxia-induced chemoreceptor inhibition in comparison to conditions of normoxia and tonic chemoreceptor activity.…”
Section: Introductionmentioning
confidence: 99%